Leadership studies the dialogue of disciplines (Cheltenham Edward Elgar Pub, 2011)
This unique, cross-disciplinary volume encourages a new synthesis in the vibrant field of leadership studies. Comprising reflective conversations among scholars from different disciplines, the contributors explore common ground for new research and ideas.
Includes bibliographical references and indexes.
Keywords: Leadership --Research.